(3GdcGajIs - (3CHh YeQh, Hf GdMGLH, LeGd GdOjf, YKeGf Hf YeQ Hf CHj HcQ Hf jhfS, J (B644(3g`s ((3eMeO TajY Hf OYhGOGQs)
(3ChdgG (B:s
(3HSe Gddg (B... (3GdcdeI daX hVY deYfi eaQO hgj GSe haYd hMQa dCfgG EeG Cf JOd Ydi eYfi aj faSgG Ch dG , GdKGfj MQa hGdChd EeG Cf jbJQf HCMO GdCRefI GdKdGKI ChdG GdKGfj GdGSe hGdChd GdaYd (B...s
(3BNQgG (B:s
... (3hEf de jcf acGdeJUd hef Ke bjd gd JQjqf hJQhqf hJQjqf , hGZRhqf hCZoRqf hCZpRqf hGdeNaaI JMPa ddSGcfjf aj Gdhba ajQO eG MPa hGdaJhM eG bHdgG JbdH CdaG (B. (3bO Jes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B4\211s
(3cTa GdXfhf (B2\1370s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdfMhs